Penelitian Dan Pengembangan Katalog Keanekaragaman Serangga Polinator Nanas Untuk Materi Keanekaragaman Hayati Siswa SMA - Lutfi Anjar Yogi Pratiwi; Dian Puspita Anggraini; Marinda Sari Sofiyana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
One way to develop learning media is create a catalog based on the local potential of pineapple plantations in Blitar. The aim of this work is to find out the usability of the compiled catalog as a teaching tool for biodiversity material. This study uses the Research and Development (RnD) research method referred to Sugiyono (2017), starting with potential problem analysis, data collection, product design, design validation, and then design review. The tools used by the researchers consisted of validation surveys of media, materials and language experts. The data collected by the researchers were analyzed using quantitative descriptive data analysis techniques. Based on the results of validity tests by media experts, 93% feasibility was achieved with highly feasible criteria, 94% with material experts, and 89% with language experts. The conclusion is the catalog of pineapple pollinator diversity in Blitar feasibility was achieved as a teaching tool.